Electrochemical properties study on NCM622 by in suit modification of Mg and F. (August 2020) - He, Rui; Bai, Xue; Wei, Aijia; Zhang, Lihui; Liu, Zhenfa
Abstract: With the rapid development of portable electronic products and electric cars, higher requirements are put forward for the performance of high energy density lithium ion battery. Nickel-rich layered metal oxides with higher energy density and lower raw material cost are considered as ideal cathode materials for lithium ion batteries. However, the structural defects and unstable interfacial chemical properties make the electrochemical properties degrade and reduce the safety of the material. Based on the previous work, this project synthesized NCM622 materials by solid phase method, and studied the influence of F, Mg and MgF2 on the comprehensive electrochemical properties of NCM622 materials. The relationship between microstructure and electrochemical properties of the materials was studied..